Profile and outcomes of acute myocardial infarction amongst young South Africans - Hoosain, Shakeel (Department of Medicine, 2026)
Background Acute myocardial infarction (AMI) is a leading cause of death worldwide; however, little is known about the clinical profile and outcomes in South Africans under the age of 45 years with AMI. Therefore, we aimed to compare the clinical profile and outcomes of patients younger and older than 45 years treated for AMI at a South African tertiary centre. Method We reviewed the hospital records of all patients admitted with AMI to the Coronary Care Unit at Groote Schuur Hospital, Cape Town in 2016. Poor outcome was defined as death, readmission with heart failure or an acute coronary syndrome (ACS) within 12 months of the index presentation. Results This study included 302 patients, of which 48 (15.9%) were younger than 45 years. A third of the young cohort had premature coronary artery disease. Smoking was the most common risk factor amongst young patients (72.2%). In terms of metabolic risk factors, the older cohort was more likely to have hypertension (68.9% vs 52.1%, p=0.024) and dyslipidaemia (49.6% vs 31.2%, p=0.019). Albeit common in both cohorts, there was no significant difference in prevalence between diabetes mellitus or smoking history. The older cohort was more likely to have poorer outcomes (27.2% vs 6.2%, p=0.002), a significantly higher prevalence of death (10.1% vs none, p=0.033) and readmission for either heart failure or ACS (18.9% vs 6.2%, p=0.032). Page 8 of 27 Conclusion We showed significant differences in the risk factor profile and outcomes of young patients with AMI compared to older counterparts, however, traditional risk factors for coronary artery disease remained common. This highlights the importance of implementing prevention strategies for AMI at earlier ages in South Africa.